Molecular insights of Carbapenem resistance Klebsiella pneumoniae isolates with focus on multidrug resistance from clinical samples. Issue 1 (January 2021) - Indrajith, Sureka; Mukhopadhyay, Asish Kumar; Chowdhury, Goutam; Farraj, Dunia A. Al; Alkufeidy, Roua M.; Natesan, Sivakumar; Meghanathan, Velmurugan; Gopal, Selvakumar; Muthupandian, Saravanan
Abstract: Background: Carbapenem are the last-line antibiotic, defence against Gram-negative extended spectrum ß-lactamases producers (ESBLs). Carbapenem resistance Enterobacteriaceae especially Carbapenem resistant- Klebsiella pneumoniae (CR-KP) is recognized as one of the well-known public health problem, which is increasingly being reported around the world. The present study was focused to analyse the prevalence and characterization of antibiotic resistance K. pneumoniae in centre region of Tamil Nadu, India. Methodology: Totally 145 suspected K. pneumoniae isolates [Urine, Pus, Sputum, Blood and Biopsy] obtained from hospitals of Central South India. The isolates were subjected to biochemical and molecular identification technique, following with antibiotic resistance pattern by standard antibiotic sensitivity test. Multidrug resistance (MDR) with β-lactamase producing Carbapenem resistant K. pneumoniae (CR-KP) strains were screened by classical sensitivity method and also drug resistance encoded gene. Also, molecular typing of the MDR strains were characterized by Pulsed-Field Gel Electrophoresis (PFGE). Further, the outer membrane protein ( OmpK35 and 36) related Carbapenem resistance were characterized. Results: Totally, 61% of isolates were confirmed as K. pneumoniae, 75 % of isolates were MDR including 58% carbapenem and 97% ESBL antibiotics and grouped into 17 distinct resistant patterns. The MDR KP isolates shows positive for blaCTXM-1 (92 %) gene followed by blaSHV (43 %), blaTEM (36 %), blaNDM-1 (26 %), blaGES (20 %) and blaIMP-1 (8 %). Moreover, 62 % CR-KP isolates loses OmpK36 and 33% isolates loses OmpK35 . Conclusions: Loss of OmpK36 were highly an influence the cefoxitin and carbapenem resistance. Sixteen different PFGE patterns have been observed among the 18 MDR isolates. Eventually, ESBL as well as CR-KP were diverse in genetic makeup and often associated with hyper virulence hvKP should be of serious concern.